2011
DOI: 10.3109/17477166.2010.517313
|View full text |Cite
|
Sign up to set email alerts
|

Industry self regulation of television food advertising: Responsible or responsive?

Abstract: While some companies have responded to pressures to reduce unhealthy food advertising on television, the impact of the self-regulatory code is limited by the extent of uptake by food companies. The continued advertising of unhealthy foods indicates that this self-regulatory code does not adequately protect children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
71
1
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(77 citation statements)
references
References 11 publications
2
71
1
3
Order By: Relevance
“…Twenty-eight studies collected data or obtained commercial monitoring data on food advertising, and used this information to assess advertising content, usually over time, to determine the success of actions (Adams et al, 2012;AFGC, 2012;ASC, 2010;Batada and Wootan, 2009;Brindal et al, 2011;Effertz and Wilcke, 2012;EU Pledge, 2010, 2011, 2012FTC, 2012;Hebden et al, 2011;Kim et al, 2012;King et al, 2011;Kolish and Hernandez, 2012;Kunkel et al, 2009;Ofcom, 2008Ofcom, , 2010Potvin Kent et al, 2011b;Powell et al, 2010;Quilliam et al, 2011;Rudd Center, 2010a, 2010b, 2011, 2012a, 2012bSpeers et al, 2011;Taras and Gage, 1995). The aim of these studies was to determine whether advertising content had changed as new actions were implemented.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Twenty-eight studies collected data or obtained commercial monitoring data on food advertising, and used this information to assess advertising content, usually over time, to determine the success of actions (Adams et al, 2012;AFGC, 2012;ASC, 2010;Batada and Wootan, 2009;Brindal et al, 2011;Effertz and Wilcke, 2012;EU Pledge, 2010, 2011, 2012FTC, 2012;Hebden et al, 2011;Kim et al, 2012;King et al, 2011;Kolish and Hernandez, 2012;Kunkel et al, 2009;Ofcom, 2008Ofcom, , 2010Potvin Kent et al, 2011b;Powell et al, 2010;Quilliam et al, 2011;Rudd Center, 2010a, 2010b, 2011, 2012a, 2012bSpeers et al, 2011;Taras and Gage, 1995). The aim of these studies was to determine whether advertising content had changed as new actions were implemented.…”
Section: Methodsmentioning
confidence: 99%
“…Seven out of the 18 studies indicated that self-regulation had reduced the volume of, exposure to and expenditure on advertising for foods HFSS for the majority of outcome measures (Batada and Wootan, 2009;FTC, 2012;Hebden et al, 2011;King et al, 2011;Powell et al, 2010;Rudd Center 2010b, Speers et al, 2011. The remaining studies reported that self-regulation did not have the desired impact on the majority of outcome measures (Brindal et al, 2011;Effertz and Wilcke, 2012;Kunkel et al, 2009;Potvin Kent et al, 2011a, 2011b, 2012Quilliam et al, 2011;Rudd Center 2010a, 2011, 2012a, 2012b.…”
Section: Self-regulatory Actionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although participating companies tended to be among the largest in their markets and/or for their products, there are many more companies that manufacture foods of interest for children who did not participate in the pledges; a recent analysis in Australia found that only fourteen of the forty-one companies that engaged in advertising food to children through TV participated in the national pledge programme (12) . This limitation is particularly notable at the global level.…”
Section: Pledge Coveragementioning
confidence: 99%